2015
DOI: 10.4102/sajbm.v46i2.93
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation by motivation of tourists to the Kgalagadi Transfrontier Park

Abstract: The Kgalagadi Transfrontier Park is one of South Africa's unique attractions for national and international tourists. However, little research has been done on visitors to transfrontier parks. In addition marketers highlight the importance of understanding the reasons why people travel and who these tourists are. Therefore the aim of this article is to segment the market of the Kgalagadi Transfrontier Park by means of visitors' travel motives. This was achieved by means of a survey. In the statistical analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Similar to other studies (e.g., see Saayman and Dieske, 2015;Buckely, 2012), nature, risk, contemplation and socialization emerged as the most relevant motivational factors to bring adventure tourists to protected areas. Regarding behavioural intention, descriptive statistics were used to evaluate mean and standard deviation.…”
Section: Source: Authors' Data and Calculationssupporting
confidence: 83%
“…Similar to other studies (e.g., see Saayman and Dieske, 2015;Buckely, 2012), nature, risk, contemplation and socialization emerged as the most relevant motivational factors to bring adventure tourists to protected areas. Regarding behavioural intention, descriptive statistics were used to evaluate mean and standard deviation.…”
Section: Source: Authors' Data and Calculationssupporting
confidence: 83%
“…Collectively, the findings of these studies indicate that visitors to national parks are homogeneous in terms of their sociodemographic profile: they are mainly from Gauteng (the economic hub of the country), in their forties, well educated, prefer longer lengths of stay and have considerable spending power (Engelbrecht, Kruger & Saayman 2014;Kruger, Saayman & Hermann 2014;Kruger et al 2017). Previous research conducted on the motives of these visitors identified the push factor, escape from the daily routine (Botha, Saayman & Kruger 2016;Hermann et al 2016;Kruger, Saayman & Saayman 2010;Kruger et al 2017;Saayman & Dieske 2015). Other push motives consistent across the board include factors such as novelty (Kruger et al 2010 (Viviers & Slabbert 2012).…”
Section: Motives Of Visitors To Captive Wildlife Settingsmentioning
confidence: 99%
“…Other push motives consistent across the board include factors such as novelty (Kruger et al 2010 (Viviers & Slabbert 2012). Pull factors include education and learning about nature (Botha et al 2016;Kruger et al 2010;Saayman & Dieske 2015), participating in recreational and leisure activities (Hermann et al 2016), as well as the park attributes, nature experiences and photography (Kruger et al 2010).…”
Section: Motives Of Visitors To Captive Wildlife Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several papers that discuss tourism recommendations, but only focus on 1 tourist spot or tourist attraction category: Restaurants [4,5], Museums [6][7][8][9][10], Spa Resorts [11][12][13], Beaches [14], Parks [15], Nature-based Activities [16,17], Hotels [18,19], Movies [20,21].…”
Section: Introductionmentioning
confidence: 99%